2006
DOI: 10.1111/j.1365-2265.2006.02578.x
|View full text |Cite
|
Sign up to set email alerts
|

Lower ability to oxidize lipids in adult patients with growth hormone (GH) deficiency: reversal under GH treatment

Abstract: The GH-deficient patients exhibited a highly significant shift in the balance of substrate oxidation during exercise, towards a decrease in fat oxidation, and a shift towards lower intensities of the crossover (52 +/- 5.5%vs. 72.6 +/- 6.6% of Wmax th, P < 0.03) and maximal fat oxidation (131.04 +/- 14 vs. 234.4 +/- 30.1 mg/min, P < 0.03) in the GHD and control groups, respectively. However, GH treatment at 6 and 12 months partially reversed this defect, resulting in an increase (+83%, P < 0.001) in the maximal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2008
2008
2012
2012

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…Under resting conditions there was no effect of GH, while during and following 45 min of exercise at lactate threshold there was a greater increment in fatty acid turnover following GH administration. A more recent study has also demonstrated an increase in maximal fat oxidation during exercise in GHD adults following 6 and 12 months GH replacement [83].…”
Section: Substrate Metabolismmentioning
confidence: 92%
See 1 more Smart Citation
“…Under resting conditions there was no effect of GH, while during and following 45 min of exercise at lactate threshold there was a greater increment in fatty acid turnover following GH administration. A more recent study has also demonstrated an increase in maximal fat oxidation during exercise in GHD adults following 6 and 12 months GH replacement [83].…”
Section: Substrate Metabolismmentioning
confidence: 92%
“…In the study of Gibney et al [81], plasma glucose levels were greater under resting and exercise conditions during GH replacement, while in the study of Kanaley et al [82] where a stable isotope glucose tracer was used, there was no discernible effect of GH on the rate of glucose appearance into or disappearance from the circulation. GH replacement did not alter glucose oxidation during exercise in the study of Brandou et al [83].…”
Section: Substrate Metabolismmentioning
confidence: 97%
“…Growth hormone inhibits lipoprotein lipase in adipose tissue,28,29 reduces de novo lipogenesis in the liver,30 and increases overall fat oxidation rates,31 which may contribute to its positive effects on lipids. Consistent with these known physiological effects of GH, we found that GH administration in patients with HIV and relative GHD (1) decreased abdominal visceral fat and trunk fat, (2) increased lean body mass, and (3) reduced triglycerides.…”
Section: Commentmentioning
confidence: 99%
“…The maximal fat oxidation rate (MFO) has been expressed in mg/min (Perez-Martin & Mercier, 2001;Dumortier et al, 2002;Brandou et al, 2003Brandou et al, , 2005Brandou et al, , 2006aBrandou et al, , 2006b), g/min (Achten et al, 2003;Achten & Jeukendrup, 2004;Jeukendrup, 2003), mg/min/kg body weight, mg/min/kg fat free mass, and more recently in mg/min/kg muscle mass (Lavault et al, 2011). Muscle can be evaluated from bioimpedance analysis with a validated equation (Janssen et al, 2000), and expression of MFO in mg/min/kg muscle offers at least two advantages: it helps to delineate the effects of training on muscle mass and on the ability of www.intechopen.com Measurement and Physiological Relevance of the Maximal Lipid Oxidation Rate During Exercise (LIPOXmax) 11 each kg of muscle to burn lipids; it provides an index which has been shown to be predictive of the effects of exercise on weight loss (Lavault et al, 2011) as indicated below.…”
Section: Methodological Aspectsmentioning
confidence: 99%
“…Leptin increases muscle fat oxidation and decreases muscle fat uptake, thereby decreasing intramyocellular lipid stores (Dick, 2009). Although the information on this issue remains limited, it is clear that the level of maximal oxidation of lipids is related to some of these hormonal regulators : norepinephrine, whose training induced changes are positively correlated to an improvement in LIPOXmax (Bordenave et al, 2008) and growth hormone, whose deficit decreases it, a defect that can be corrected by growth hormone replacement (Brandou et al, 2006a). Downstream GH, IGF-I has also been reported to be correlated to LIPOXmax in soccer players as shown on Fig 5 ( Brun et al, 1999), reflecting either a parallel effect of training on muscle fuel partitioning or IGF-I release, or an action of IGF-I (or GH via IGF) on muscular lipid oxidation.…”
Section: The Physiological Basis For Measuring Lipid Oxidation Duringmentioning
confidence: 99%